1991
DOI: 10.1136/emj.8.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Minor procedures in the accident and emergency department: can Entonox help?

Abstract: SUMMARYThe efficacy of Entonox as a supplement to local anaesthesia for minor surgical procedures was studied. Eighty-five patients undergoing surgery for the incision and drainage of a subcutaneous abscess using a local anaesthetic were involved in a trial to ascertain the level of pain associated with such procedures and to investigate the possibility of using on-demand Entonox to supplement the local anaesthesia provided. Patients received either the standard local anaesthesia, or, alternatively, the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Given its limited side effects with short-term administration of this drug, its use in other hospital settings should be considered. A number of studies 12,13,[17][18][19] have compared nitrous oxide/oxygen and opioids and have reported on nitrous oxide's relative efficacy and safety in emergency setting. In our study we compared the analgesic efficacy and side effects of nitrous oxide/oxygen with a single dose of fentanyl in ED patients suffering isolated extremity trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Given its limited side effects with short-term administration of this drug, its use in other hospital settings should be considered. A number of studies 12,13,[17][18][19] have compared nitrous oxide/oxygen and opioids and have reported on nitrous oxide's relative efficacy and safety in emergency setting. In our study we compared the analgesic efficacy and side effects of nitrous oxide/oxygen with a single dose of fentanyl in ED patients suffering isolated extremity trauma.…”
Section: Discussionmentioning
confidence: 99%
“…11 12 [level 2b]. It has also been used for the relief of pain from musculoskeletal injuries, wound care, suture removal, ureteric colic, acute abdominal pain, 13 [level 2b] and some uncomfortable diagnostic procedures.…”
Section: [Level Of Evidence 2b]mentioning
confidence: 99%
“…1 Both of these can be painful, and may produce lasting effects necessitating close monitoring for extended periods. In addition to pain, such procedures may produce significant anxiety, 2 generating unpleasant memories for the patient and making the performance of the procedure difficult for the health care provider.…”
mentioning
confidence: 99%